تفكيك أدوار الشخصيات في رواية "حمار الحكيم" لتوفيق الحكيم - Shobron, Muhammad (Journal of Arabic Language and Literature (ALLAIS), 2022)
This study examines the role of several characters in the novel Himar Al Hakim by Taufiq Al Hakim with a deconstruction approach strategy. The purpose of this study is to determine the transformation of the role of the characters formed in the novel Himar Al Hakim by Taufiq Al Hakim through the interpretation using the deconstruction approach. This research uses descriptive qualitative research. In this study, researchers used document analysis as a data collection technique. To check the validity of the data, researchers used persistence techniques in observation. The data analysis technique in this study will use content analysis techniques. After applying deconstruction of meaning through contradictory meanings in Himar Al Hakim's novel, it is found that Beik as a well-known writer has several bad traits based on his daily behavior, such as not listening to other people's words, disrespecting others, not having a firm stand, a person who lazy, and always shy away from responsibility. Also found were several roles of marginal figures who could become important figures because they motivated Beik through these important roles, namely the director, haji, and the cameraman's wife.